Composición bromatológica del quiebra barriga (trichanthera gigantea) en condiciones edáficas de la estación experimental “El Padmi” de la Universidad Nacional de Loja - Pogo Jiménez, Luis Enrique (2023)
The implementation and use of plant species for animal feed has been the subject of numerous investigations in various countries. The study was implemented at the El Padmi experimental station of the National University of Loja, located in the "Los Encuentros" parish, Yantzaza canton, Zamora Chinchipe province, which aimed to carry out the nutritional assessment of Quiebra barriga (Trichanthera gigantea), as Supplement for bovine feeding in small and medium-sized farms in the province of Zamora Chinchipe. The bromatological composition of leaves, stems and stems plus leaves of 300 plants will be released in three cutting periods: 60, 120 and 180 days applying the AOAC protocols, (2000), digestibility of organic matter and energy content, through procedure suggested by Menken et al (1979) modified by Rodríguez et al (2014) taking protein values and gas production from Nacedero at 24 h (34.2 ml). The results of the variables under study were subjected to an analysis of variance with a completely randomized design. In the necessary cases, the Tukey test was applied at the 0.05 level of significance for the comparison of means. The results showed a statistical difference (p<0.0001) between the cutting periods for PC, FDN, FDA, EM, DMO and LG (leaves and stems plus leaves being), MS, Cz (leaves), LG (stems) showed no difference. each other. It is concluded that the cutting age influences the nutritional characteristics of Trichanthera gigantea. Key words: Trichanthera gigantea, chemical composition, age of cut, digestibility.